The lipid accumulation product is a powerful tool to diagnose metabolic dysfunction-associated fatty liver disease in the United States adults - Li, Hejun; Zhang, Ying; Luo, Hengcong; Lin, Rong (Frontiers in Endocrinology, 2022)
Abstract: Background ＆ Objectives: Body mass index (BMI) and waist circumference (WC) are widely used to assess obesity, but they are limited in distinguishing complicated body metabolic situations (fat mass, lean body mass, visceral and subcutaneous fat deposits in the abdomen). The purpose of this study was to evaluate the diagnostic efficacy of different anthropometric indices in metabolic dysfunction associated fatty liver disease (MAFLD) and to identify the best cut-off point for the diagnosis of MAFLD in United States adults. Methods: A cross-sectional study among 4195 participants over 18 years old in the National Health and Nutrition Examination Survey (NHANES) 2017-2018 was performed. All patients underwent vibration controlled transient elastography (VCTE). Assess the anthropometric measurements, including BMI, WC, waist-to-height ratio (WHtR), waist-to-hip ratio (WHR), cardiometabolic index(CMI)，triglyceride-glucose (TyG) index, hepatic steatosis index (HSI), lipid accumulation product (LAP), body roundness index (BRI), visceral fat index (VAI), abdominal volume index (AVI), cone index (CI), and body fat index (BAI). Logistic regression analyses were conducted to estimate the impact of these indices the on odds ratio (OR) values of MAFLD. Receiver operator characteristic (ROC) analyses were performed to assess the diagnosing capacity of these anthropometric indices for MAFLD and identify the optimal cut-offs points. Results: A total of 4195 (2069 men and 2126 women) participants were performed, with 45.4 ± 0.64 (mean ± SD) years old. All anthropometric metrics were positively associated with MAFLD, irrespective of whether it was treated as a continuous or categorical variable (P<0.05). Multivariate logistic regression showed a positive correlation between AVI, HSI, WHtR, BRI and MAFLD, with significant interaction with gender. ROC curves results showed that LAP had the highest AUC [0.813 (95% CI, 0.800-0.826)]. Furthermore, LAP showed the highest ROC in both the training set [0.812 (95% CI, 0.800-0.835)] and the validation set [0.809 (95% CI, 0.791-0.827)]. Conclusions: In the present study, we showed that those anthropometric indices were significant associated with MAFLD in United States adults. Besides, the association of HSI, BRI, AVI and WHtR with MAFLD was more obviously in men than in women. LAP may be a sensitive marker for diagnosing MAFLD in U.S. adults